Endometrial Cancer Stem Cell as a Potential Therapeutic Target - Kyo, Satoru; Kato, Kiyoko (Seminars in Reproductive Medicine, 2015)
Adult stem cells have recently been identified in several types of mature tissue and it has been also suggested that stem-like cells exist in cancerous tissues. It is believed that many cancer stem cells (CSCs) upregulate the expression of drug transporters, allowing them to efficiently pump antitumor agents out of the cells. CSCs reside in a quiescent state, making them resistant to chemotherapeutic agents that target rapidly cycling cells. They are also endowed with a more invasive and metastatic phenotype. These results indicate the requirement to develop a new target treatment for CSCs. There are several methods for the identification of CSCs; for example, detection by CSC markers, such as CD133, CD44, CD117(c-kit), aldehyde dehydrogenase 1 (ALDH1), and isolation of side population (SP), which are identified based on their ability to remove intracellular Hoechst 33342, a fluorescent dye. Here, we review recent articles that show the presence of stem cells in endometrial cancer and introduce the results of our own recent studies using CD133 or CD117 positive cells and SP cells.
Keywords: endometrium; stem cells; endometrial cancer; therapeutic target